Luminescence and scintillation properties of Ce3+-doped SiO2–Al2O3–BaF2–Gd2O3 glasses - Chewpraditkul, Weerapong; Pattanaboonmee, Nakarin; Yawai, Nattasuda; Chewpraditkul, Warut; Lertloypanyachai, Prapon; Sreebunpeng, Krittiya; Yoshino, Masao; Liu, Liwan; Chen, Danping (Optical materials, 2019)
Ce3+-doped glasses with composition of (65-x)SiO2 − 20Al2O3 –15BaF2 -xGd2O3 (x = 5, 10, 15, 20 and 25) were synthesized under CO atmosphere by melt-quenching method. The photoluminescence (PL) emission due to Ce3+: 5d1 → 4f transition was red-shifted with increasing Gd2O3 content. The acceleration of PL decay was observed with increasing Gd2O3 content. The scintillation efficiency of about 100% of the Bi4Ge3O12 scintillator was obtained for a 10%Gd2O3 containing glass while a high light yield (LY) of 2050 photons/MeV and energy resolution of 15.8% at 662 keV γ rays was obtained for a 15%Gd2O3 containing glass. The integrating-time dependence of LY value and LY ratio (α/γ ratio) under excitation with α- and γ-rays were also measured. •Scintillation properties of Ce3+-doped Gd2O3 containing glasses were investigated.•Decay time shortening was achieved with increasing Gd2O3 content.•High RL intensity comparable to BGO was obtained for 10% Gd2O3 containing glass.•Light yield of 2100 photons/MeV was obtained for 15% Gd2O3 containing glass.